Progressive and developmental pathways for student retention and academic success: Lessons from one-on-one student academic advising - Emekako, R.; van der Westhuizen, S. (South African Journal of Higher Education, 2021)
Once higher education institutions grant access to students, it is only normal that these institutions provide continual support using appropriate frameworks which consider both academic- and social-related challenges students face. This practice-based study portrays the role played by the Centre for Teaching and Learning (CTL) at a traditional-based university in South Africa in the provision of excellent and innovative, research-informed guidance and support in teaching and learning to students in a contemporary higher education context. More specifically, the article was theorised from “intentional” academic advising (AA) as an approach that informs AA practices and thus leads to progressive academic improvement, retention and success of students through one-on-one AA consultations. Two sets of samples were used to account for the improvement of academic performance emanating from consultations. Anonymity and confidentiality were ensured to protect participating students’ personal information. The findings revealed that, through the application of the “intentional” process (through the knowledge of theories on student development, experiences of advisers and student background), variable academic gain was reached in student advising. Although first-year students consulted more, most academic gain was experienced by exiting third-year students, particularly when they requested help on study methods in higher education. It is concluded that an enlarged and more comprehensive dataset (which includes across-campus data) and a qualitative pooling of the experience of academic advisers across campuses would allow for better understanding of the influence of AA practice on academic success. It is recommended that the “intentional” process be applied consciously and be used in professionalising advisers. Finally, it is also recommended that a study be conducted to look into the influence of all components of the support framework within the institution on a cohort depicting the diverse background of students enrolled in the institution.